2018
DOI: 10.20961/seeds.v1i1.19894
|View full text |Cite
|
Sign up to set email alerts
|

Metacognitive Learning Strategy: In Search of Theoretical Model for Reading Comprehension

Abstract: <p>This paper was presented on the basic of senior high school teachers’ complaint over the implementation of scientific- based approach in 2013 Indonesian National Curriculum. Their path to successful learning is obstructed by the discontinuity of five stages of scientific- based approach which comprises of observing, questioning, associating, experimenting, and networking. This study was aimed at developing a theoretical model of reading comprehension based on metacognitive learning strategies. Descrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
1
2
0
1
Order By: Relevance
“…The findings emerging from the present enquiry indicated that CT awareness-raising and MC training could boost the participants' reading comprehension of general and argumentative texts and that CT failed to enhance their comprehension of texts expressing causal relationship. As far as the effect of metacognitive training is concerned, the outcomes of the current investigation are in conformity with some previous inquiries (Aghaie & Zhang, 2012;Akkakoson & Setobol, 2009;Estacio, 2013;Ismail & Tawalbeh, 2015;Jafari & Ketabi, 2012;Karbalaei, 2011;Mehrpour, Sadighi, & Bagheri, 2012;Riyadi et al, 2017;Shih & Huang, 2018) that confirmed facilitative effects of MC training on EFL learners' reading comprehension.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The findings emerging from the present enquiry indicated that CT awareness-raising and MC training could boost the participants' reading comprehension of general and argumentative texts and that CT failed to enhance their comprehension of texts expressing causal relationship. As far as the effect of metacognitive training is concerned, the outcomes of the current investigation are in conformity with some previous inquiries (Aghaie & Zhang, 2012;Akkakoson & Setobol, 2009;Estacio, 2013;Ismail & Tawalbeh, 2015;Jafari & Ketabi, 2012;Karbalaei, 2011;Mehrpour, Sadighi, & Bagheri, 2012;Riyadi et al, 2017;Shih & Huang, 2018) that confirmed facilitative effects of MC training on EFL learners' reading comprehension.…”
Section: Discussionsupporting
confidence: 91%
“…Metacognitive training was also found effective in enhancing less proficient and low accomplishing students' learning (Ismail & Tawalbeh, 2015). In another study, Riyadi, Hersulastuti, and Nugrahaningsih (2017) developed a theoretical model of reading comprehension based on MCSs and found underlining, note-taking, abridging, and idea mapping as significantly enhancing senior secondary school students' comprehension. More recently, Shih and Huang (2018) underscored the number and variety of MCSs used by the students as major determinants of reading performance during reading testing situations.…”
Section: Mcss and Reading Comprehensionmentioning
confidence: 98%
“…Models of teaching students metacognitive strategies in order to perform better in comprehension test have been addressed in recent studies, particularly by Phakiti (2003) on the example of the Thai students' questionnaire results, retrospective interviews and an EFL achievement test. Similarly, a theoretical metacognitive strategies application model of reading comprehension was suggested by Riyadi et al (2017), who highlighted underlining, note-taking, abridging, and idea mapping as significantly facilitative techniques. The findings from the recent study by Davoud Amini1, Mostafa Hosseini Anhari and Abolfazl Ghasemzadeh (2020) provide further conceptual support for dynamic models of self-regulated action and practical implications regarding the complementary role of metacognitive and self-regulatory engagements in reading development.…”
Section: Literature Reviewmentioning
confidence: 99%
“…SegúnNaimnule & Corebina (2018) conceptúan como conciencia de los aspectos del pensamiento de orden superior que tiene un control activo que se implica en el proceso del aprendizaje. Esto quiere decir que la metacognición se ocupa de guiar los procesos del aprendizaje reflexionando, comprendiendo y controlando los aprendizajes(Saks & Leigen, 2018) A esto se une la regulación metacognitiva que son acciones que facilitan a los estudiantes el control de sus aprendizajes(Oguz & Ataseven, 2016) Riyadi, Hersulastuti & Nugrahaningsih (2017). plantean tres habilidades reguladoras como son la planificación, monitoreo y evaluación.…”
unclassified